High frequency oscillations associate with neuroinflammation in low-grade epilepsy associated tumors. (January 2022) - Sun, Dongqing; van Klink, Nicole E.C.; Bongaarts, Anika; Zweiphenning, Willemiek E.J.M.; van 't Klooster, Maryse A; Gebbink, Tineke A; Snijders, Tom J; van Eijsden, Pieter; Robe, Pierre A.J.T.; Aronica, Eleonora; Zijlmans, Maeike
Highlights: This is the first study to directly compare high frequency oscillations and inflammatory markers that contribute to epileptogenesis. Increased ripple rates correlate with increased IL1β/HMGB1/TLR4 pathway activity in the peritumoral tissue of low-grade tumors. Tumors that generate ripples are infiltrated by more CD3-positive T-cells than tumors without ripples. Abstract: Objective: High frequency oscillations (HFOs) in intraoperative electrocorticography (ioECoG) are thought to be generated by hyperexcitable neurons. Inflammation may promote neuronal hyperexcitability. We investigated the relation between HFOs and inflammation in tumor-related epilepsy. Methods: We identified HFOs (ripples 80–250 Hz, fast ripples 250–500 Hz) in the preresection ioECoG of 32 patients with low-grade tumors. Localization of recorded HFOs was classified based on magnetic resonance imaging reconstructions: in tumor, in resected non-tumorous area and outside the resected area. We tested if the following inflammatory markers in the tumor or peritumoral tissue were related to HFOs: activated microglia, cluster of differentiation 3 (CD3)-positive T-cells, interleukin 1-beta (IL1β), toll-like receptor 4 (TLR4) and high mobility group box 1 protein (HMGB1). Results: Tumors that generated ripples were infiltrated by more CD3-positive cells than tumors without ripples. Ripple rate outside the resected area was positively correlated with IL1β/TLR4/HMGB1 pathway activity in peritumoral area. These two areas did not directly overlap. Conclusions: Ripple rates may be associated with inflammatory processes. Significance: Our findings support that ripple generation and spread might be associated with synchronized fast firing of hyperexcitable neurons due to certain inflammatory processes. This pilot study provides arguments for further investigations in HFOs and inflammation.